2022
DOI: 10.1371/journal.pone.0262661
|View full text |Cite
|
Sign up to set email alerts
|

Robust and generalizable embryo selection based on artificial intelligence and time-lapse image sequences

Abstract: Assessing and selecting the most viable embryos for transfer is an essential part of in vitro fertilization (IVF). In recent years, several approaches have been made to improve and automate the procedure using artificial intelligence (AI) and deep learning. Based on images of embryos with known implantation data (KID), AI models have been trained to automatically score embryos related to their chance of achieving a successful implantation. However, as of now, only limited research has been conducted to evaluat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 53 publications
0
55
0
Order By: Relevance
“…For example, embryo developmental speed, morphokinetic parameters, and blastocyst grade [ 21 , 40 , 46 , 47 ] have been reported to correlate with both sex ratio and implantation likelihood. In a study on iDAScore, it was shown that scores correlate with both time to blastocyst and blastocyst grades [ 30 ]. This could possibly be one of the causes for the observed non-significant trend in the male sex ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, embryo developmental speed, morphokinetic parameters, and blastocyst grade [ 21 , 40 , 46 , 47 ] have been reported to correlate with both sex ratio and implantation likelihood. In a study on iDAScore, it was shown that scores correlate with both time to blastocyst and blastocyst grades [ 30 ]. This could possibly be one of the causes for the observed non-significant trend in the male sex ratio.…”
Section: Discussionmentioning
confidence: 99%
“…This is different from the current study where the test data set only includes transferred embryos and specifically discarded embryos are not included in the AUC calculation. In the analysis of iDAScore v1.0 by Berntsen et al [ 30 ], the AUC for FHB + vs (FHB − and discarded) was 0.95 and for FHB + vs FHB − the AUC was 0.67. The differences between these two AUC values clearly show that it is much easier to discriminate between FHB + and discarded embryos than to discriminate among transferred embryos alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values, while allowing a general comparison with similar AIs described in the literature (e.g. Alife Health AI ROC-AUC 0.62-0.64, Fairtility AI ROC-AUC 0.68-0.70, Vitrolife AI ROC-AUC 0.67see Loewke et al, 2022, Erlich et al, 2022, and Berntsen et al, 2022, do not give an indication of the ability of the AI model to effectively rank embryos for selection within a patient cohort during a single IVF cycle.…”
Section: Methods Evaluating the Correlation Of Ai Score With Clinical...mentioning
confidence: 99%
“…In recent years there has been a growing interest in the use of artificial intelligence (AI) to support embryo quality assessment, with numerous algorithms being developed for analysis of static images or time-lapse videos of embryos to aid in the selection of embryos for transfer (Berntsen et al, 2022;Chavez-Badiola et al, 2020;Erlich et al, 2022;Khosravi et al, 2019;Loewke et al, 2022;Silver et al, 2020;Tran et al, 2019;VerMilyea et al, 2020). However, due to the infancy of AI in the embryology field, few of these studies have evaluated real-world clinical use.…”
Section: Introductionmentioning
confidence: 99%